Multi-polymer, preparation method thereof, polymer electrolyte and solid lithium ion battery
A multi-polymer electrolyte with enhanced ionic conductivity and voltage resistance addresses safety and performance issues in lithium-ion batteries by combining specific structural units, improving conductivity and stability.
Patent Information
- Application Number
- CN202310687215.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-09
- Publication Date
- 2024-12-17
AI Technical Summary
Current all-solid-state polymer-based electrolytes in lithium-ion batteries suffer from low room temperature ionic conductivity, low electrochemical window, and inability to withstand high voltage, posing safety risks due to flammability and leakage.
A multi-polymer electrolyte composed of structural units with strong polar groups and high voltage resistance characteristics, combined through specific monomer reactions, enhancing ionic conductivity and electrochemical stability.
The multi-polymer electrolyte achieves high room temperature ionic conductivity, a wide electrochemical window, and improved safety by preventing flammability and leakage, suitable for high-voltage battery systems.
Smart Images

Figure CN119143923A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a multi-component copolymer and a preparation method thereof, a polymer electrolyte and a solid lithium ion battery. Background Art
[0002] Lithium-ion batteries are widely used due to their high energy density, long cycle life, high output voltage, no memory effect, recyclability, and environmental friendliness. In recent years, the development of new energy vehicles and other fields has put forward higher requirements for lithium-ion batteries, especially high-power, high-energy-density, and high-safety batteries that are in urgent need of development. Currently, commercial lithium-ion batteries generally use highly flammable, explosive, and volatile organic electrolyte components, which pose extremely high safety risks. Using all-solid-state electrolytes that do not contain any organic liquids to replace electrolytes containing highly flammable organic liquids is an important way to solve battery safety issues.
[0003] Polymer electrolytes can effectively reduce the weight of batteries, which is beneficial to the improvement of battery energy density. Polymer electrolytes have good film-forming properties and are easy to process, which is conducive to making millimeter and micrometer-level thin films, and can be made into thin-film batteries. In addition, polymer-based electrolytes have good viscoelasticity, interface advantages, and do not contain any volatile and flammable organic liquids, which can overcome the safety issues caused by battery leakage. However, polymer electrolytes currently have low room temperature ionic conductivity (10 -6 S / cm~10 -8 S / cm), low electrochemical window (3.8V Li+ / Li), and inability to withstand high voltage have greatly limited their use. The development of polymer electrolytes with high room temperature ionic conductivity and high voltage resistance is an important research direction for polymer electrolytes.
[0004] CN106992311A discloses an all-solid polymer electrolyte membrane and a preparation method thereof, wherein the all-solid polymer electrolyte membrane is based on PEO or PEO-PMMA. CN102412401A discloses an adhesive composition, an electrode and a rechargeable lithium battery for a rechargeable lithium battery, wherein the polymer electrolyte is still based on a PEO-based electrolyte based on an alkoxy chain segment, and is supplemented with nanofillers, plasticizers, etc. to form a composite electrolyte. Although a higher room temperature ionic conductivity can be obtained, it still faces the problem of being intolerant to high voltage. Summary of the invention
[0005] The purpose of the present invention is to provide a multi-polymer and its preparation method, a polymer electrolyte and a solid lithium-ion battery to address the problems of low room temperature ionic conductivity, relatively low oxidation potential, and high voltage resistance of current all-solid-state polymer-based electrolytes, as well as unsafe factors such as leakage and flammability of commercial lithium-ion batteries. The polymer electrolyte has high room temperature ionic conductivity, excellent voltage resistance characteristics, and a high electrochemical window, and can match higher voltage battery systems.
[0006] In order to achieve the above object, the first aspect of the present invention provides a multi-polymer, wherein the multi-polymer comprises structural unit A, structural unit B and structural unit C, and the multi-polymer further comprises at least one of structural unit E, structural unit F and structural unit G;
[0007] Wherein, the structural unit A has a structure shown in formula (a), the structural unit B has a structure shown in formula (b), and the structural unit C has a structure shown in formula (c);
[0008]
[0009] Wherein, in formula (a), R 1 C 2 -C 4 Alkyl; R 2 H and / or C 1 -C 4 The alkyl group;
[0010] In formula (b), R 3 One or more selected from H, F, Cl, Br, I, methyl, ethyl and phenyl; R 4 One or more selected from H, methoxy, ethoxy, cyclopentyl, phenyl and p-fluoro-substituted phenyl;
[0011] In formula (c), R 5 H and / or C 1 -C 4 Alkyl; R 6 Phenyl, C 1 -C 4 One or more of alkyl and fluoroalkyl;
[0012] The structural unit E is provided by a polymer represented by formula (II);
[0013]
[0014] Wherein, m is a natural number greater than or equal to 1;
[0015] The structural unit F is provided by a polymer represented by formula (III);
[0016]
[0017] Wherein, p is a natural number greater than or equal to 1;
[0018] The structural unit G is provided by a polymer represented by formula (IV);
[0019]
[0020] Where n is a natural number greater than or equal to 1, R 7 C 1 -C 4 of alkyl.
[0021] The second aspect of the present invention provides a method for preparing a multi-polymer, wherein the preparation method comprises:
[0022] 1) in the presence of an initiator and an organic solvent, contacting a monomer represented by formula (1), a monomer represented by formula (2) and a monomer represented by formula (3) to carry out a first reaction to obtain a first reaction product;
[0023]
[0024] In formula (1), R 1 C 2 -C 4 Alkyl; R 2 H and / or C 1 -C 4 The alkyl group;
[0025] In formula (2), R 3 One or more selected from H, F, Cl, Br, I, methyl, ethyl and phenyl; R 4 One or more selected from H, methoxy, ethoxy, cyclopentyl, phenyl and p-fluoro-substituted phenyl;
[0026] In formula (3), R 5 H or C 1 -C 4 Alkyl; R 6 Phenyl, C 1 -C 4 One or more of alkyl and fluoroalkyl;
[0027] 2) contacting the first reaction product with at least one of the monomers represented by formula (II), formula (III) and formula (IV) to carry out a second reaction to obtain a multi-component copolymer;
[0028]
[0029] Wherein, m is a natural number greater than or equal to 1;
[0030]
[0031] Wherein, p is a natural number greater than or equal to 1;
[0032]
[0033] Where n is a natural number greater than or equal to 1; R 7 C 1 -C 4 of alkyl.
[0034] The third aspect of the present invention provides a multi-polymer prepared by the above-mentioned preparation method.
[0035] A fourth aspect of the present invention provides a polymer electrolyte, wherein the polymer electrolyte comprises a polymer and a lithium salt, wherein the polymer is the multi-polymer described above.
[0036] A fifth aspect of the present invention provides a solid-state lithium-ion battery, wherein the solid-state lithium-ion battery comprises a positive electrode sheet, a separator and a negative electrode sheet, wherein the separator is a polymer electrolyte membrane prepared from the aforementioned polymer electrolyte.
[0037] Through the above technical solution, the technical solution of the present invention has the following specific advantages:
[0038] (1) From the perspective of polymer electrolyte structure design, the present invention selects a polymer monomer with a strong polar group and a polymer monomer with a high voltage resistant group for copolymerization. Preferably, a polymer monomer with a lithium ion conductive functional segment is selected for copolymerization, so that the prepared polymer electrolyte has a higher room temperature ionic conductivity, a higher electrochemical window, and a higher oxidation potential;
[0039] (2) The polymer electrolyte of the present invention is easy to mass produce and has good film-forming properties. It is expected to fundamentally solve the problems of liquid leakage and flammability of liquid lithium-ion batteries, thereby greatly improving the safety performance of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 Schematic diagram of the LSV curve of the polymer electrolyte membrane prepared in Example 1 of the present invention;
[0041] Figure 2 Schematic diagram of the LSV curve of the polymer electrolyte membrane prepared in Example 2 of the present invention;
[0042] Figure 3 It is a schematic diagram of the LSV curve of the polymer electrolyte membrane prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0043] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0044] As mentioned above, the first aspect of the present invention provides a multi-component copolymer, wherein the multi-component copolymer comprises structural unit A, structural unit B and structural unit C, and the multi-component copolymer further comprises at least one of structural unit E, structural unit F and structural unit G;
[0045] Wherein, the structural unit A has a structure shown in formula (a), the structural unit B has a structure shown in formula (b), and the structural unit C has a structure shown in formula (c);
[0046]
[0047] Wherein, in formula (a), R 1 C 2 -C 4 Alkyl; R 2 H and / or C 1 -C 4 The alkyl group;
[0048] In formula (b), R 3 One or more selected from H, F, Cl, Br, I, methyl, ethyl and phenyl; R 4 One or more selected from H, methoxy, ethoxy, cyclopentyl, phenyl and p-fluoro-substituted phenyl;
[0049] In formula (c), R 5 H and / or C 1 -C 4 Alkyl; R 6 Phenyl, C 1 -C 4 One or more of alkyl and fluoroalkyl;
[0050] The structural unit E is provided by a polymer represented by formula (II);
[0051]
[0052] Wherein, m is a natural number greater than or equal to 1;
[0053] The structural unit F is provided by a polymer represented by formula (III);
[0054]
[0055] Wherein, p is a natural number greater than or equal to 1;
[0056] The structural unit G is provided by a polymer represented by formula (IV);
[0057]
[0058] Where n is a natural number greater than or equal to 1, R 7 C 1 -C 4 of alkyl.
[0059] The inventors of the present invention have found that: the monomer of the structural unit shown in formula (b) has a strong polarity, which can promote the dissociation of lithium salts and help improve the ionic conductivity of the polymer electrolyte; the monomer of the structural unit shown in formula (c) has a high voltage resistance characteristic, which can give the polymer electrolyte membrane better voltage resistance performance and improve the electrochemical window of the polymer electrolyte.
[0060] In addition, the structural unit represented by formula (a) contains an -NCO group, which can be combined with -OH, -NH in at least one of the monomers of formula (II), formula (III) and formula (IV). 2 An addition reaction occurs to generate a polyurethane polymer (multi-polymer), which has good flexibility and film-forming properties, is helpful for the preparation of polymer electrolyte membranes, and has the function of conducting lithium ions.
[0061] According to the present invention, preferably, R 1 It is one or more of ethyl, propyl and butyl.
[0062] According to the present invention, preferably, R 2 One or more selected from H, methyl, ethyl, propyl, isopropyl, n-butyl and isobutyl, preferably H and / or methyl.
[0063] According to the present invention, preferably, R 3 One or more selected from methyl, H and F.
[0064] According to the present invention, preferably, R 4 One or more selected from H, methoxy, ethoxy and cyclopentyl.
[0065] According to the present invention, preferably, R 5 One or more selected from H, methyl, ethyl, propyl and butyl, preferably H and / or methyl.
[0066] According to the present invention, preferably, R 6Selected from phenyl, methyl, ethyl, propyl, butyl and -CF 3 One or more of, preferably methyl and / or -CF 3 .
[0067] According to the present invention, preferably, the structural unit A comes from monomer a, and the monomer a is preferably alkyl isocyanate acrylate, more preferably at least one of ethyl isocyanate acrylate, propyl isocyanate acrylate, ethyl isocyanate methacrylate and propyl isocyanate methacrylate, and most preferably ethyl isocyanate acrylate and / or ethyl isocyanate methacrylate.
[0068] According to the present invention, preferably, the structural unit B comes from monomer b, and the monomer b is preferably an acrylonitrile monomer, more preferably at least one of acrylonitrile, methacrylonitrile, 2-fluoroacrylonitrile, 2-chloroacrylonitrile, 2-phenylacrylonitrile, 3-cyclopentylacrylonitrile, 3-methoxyacrylonitrile, 3-ethoxyacrylonitrile and 3-(4-fluorophenyl)-2-acrylonitrile, and most preferably at least one of acrylonitrile, methacrylonitrile and 2-fluoroacrylonitrile.
[0069] According to the present invention, preferably, the structural unit C comes from monomer c, and the monomer c is preferably a linear unsaturated carbonate monomer, more preferably at least one of allyl methyl carbonate, allyl ethyl carbonate, allyl propyl carbonate, allyl butyl carbonate, and allyl phenyl carbonate, and most preferably at least one of allyl ethyl carbonate, allyl phenyl carbonate and allyl methyl carbonate.
[0070] According to the present invention, in the multi-polymer, the molar ratio of the structural unit A, the structural unit B and the structural unit C is (2-9): (2-21): (0.5-8), preferably ((3-8): (3-18): (0.75-5).
[0071] According to a preferred embodiment of the present invention, the multi-polymer comprises the structural unit described in formula (I), and the multi-polymer further comprises at least one of structural unit E, structural unit F and structural unit G; wherein the -NCO group in the structural unit described in formula (I) is also combined with -OH and / or -NH in at least one of structural unit E, structural unit F and structural unit G. 2 reacting; the structural unit E, the structural unit F and the structural unit G are provided by the polymer represented by formula (II), the polymer represented by formula (III) and the polymer represented by formula (IV), respectively;
[0072]
[0073] In the formula, a, b, and c are all not 0, a:b:c = (2-9): (2-21): (0.5-8), preferably ((3-8): (3-18): (0.75-5); a, b, and c correspond to the molar numbers of the structure represented by formula (a), the structure represented by formula (b), and the structure represented by formula (c), respectively.
[0074] According to the present invention, in the structural unit E provided by the polymer represented by formula (II);
[0075]
[0076] Among them, preferably, 1≤m≤20, more preferably 5≤m≤10.
[0077] According to the present invention, preferably, in the multi-polymer, the molar ratio of the structural unit A to the structural unit E is (0.5-10):1.
[0078] According to the present invention, the monomer represented by formula (II) is polyethylene glycol monomethyl ether, wherein the molar number m satisfies: 1≤m≤20, preferably 5≤m≤10.
[0079] According to the present invention, in the structural unit F provided by the polymer represented by formula (III);
[0080]
[0081] Among them, preferably, 1≤p≤20, more preferably 5≤p≤10.
[0082] According to the present invention, preferably, in the multi-polymer, the molar ratio of the structural unit A to the structural unit F is (0.5-10):1.
[0083] According to the present invention, the monomer represented by formula (III) is methoxy polyethylene glycol amine, wherein the molar number p satisfies: 1≤p≤20, more preferably 5≤p≤10.
[0084] According to the present invention, in the structural unit G provided by the polymer represented by formula (IV);
[0085]
[0086] Wherein, preferably, 1≤n≤20, more preferably 5≤n≤10;
[0087] R 7 Preferred are one or more of methyl, ethyl, propyl, isopropyl, n-butyl and isobutyl, and more preferred is methyl.
[0088] According to the present invention, preferably, in the multi-polymer, the molar ratio of the structural unit A to the structural unit G is (0.5-10):1.
[0089] According to the present invention, the monomer represented by formula (IV) is polyethylene glycol monocarboxylate. Preferably, the monomer represented by formula (IV) is selected from at least one of polyethylene glycol monoacetate, polyethylene glycol monopropionate, polyethylene glycol monoisovalerate, polyethylene glycol monobutyrate, and polyethylene glycol monohexanoate, and is more preferably polyethylene glycol monoacetate, wherein the molar number n satisfies: 1≤n≤20, more preferably 5≤n≤10.
[0090] The second aspect of the present invention provides a method for preparing a multi-polymer, wherein the preparation method comprises:
[0091] 1) in the presence of an initiator and an organic solvent, contacting a monomer represented by formula (1), a monomer represented by formula (2) and a monomer represented by formula (3) to carry out a first reaction to obtain a first reaction product;
[0092]
[0093]
[0094] In formula (1), R 1 C 2 -C 4 Alkyl; R 2 H and / or C 1 -C 4 The alkyl group;
[0095] In formula (2), R 3 One or more selected from H, F, Cl, Br, I, methyl, ethyl and phenyl; R 4 One or more selected from H, methoxy, ethoxy, cyclopentyl, phenyl and p-fluoro-substituted phenyl;
[0096] In formula (3), R 5 H or C 1 -C 4 Alkyl; R 6 Phenyl, C 1 -C 4 One or more of alkyl or fluoroalkyl;
[0097] 2) contacting the first reaction product with at least one of the monomers represented by formula (II), formula (III) and formula (IV) to carry out a second reaction to obtain a multi-component copolymer;
[0098]
[0099] Wherein, m is a natural number greater than or equal to 1;
[0100]
[0101] Wherein, p is a natural number greater than or equal to 1;
[0102]
[0103] Where n is a natural number greater than or equal to 1; R 7 C 1 -C 4 of alkyl.
[0104] According to the present invention, R 1 is one or more of ethyl, propyl and butyl;
[0105] R 2 One or more selected from H, methyl, ethyl, propyl, isopropyl, n-butyl and isobutyl, preferably H and / or methyl;
[0106] R 3 One or more selected from methyl, H and F;
[0107] R 4 One or more selected from H, methoxy, ethoxy and cyclopentyl;
[0108] R 5 One or more selected from H, methyl, ethyl, propyl and butyl, preferably H and / or methyl;
[0109] R 6 Selected from phenyl, methyl, ethyl, propyl, butyl and -CF 3 One or more of, preferably methyl and / or -CF 3 .
[0110] According to the present invention, the initiator is an oil-soluble initiator; preferably, the initiator is selected from azobisisobutyronitrile, benzoyl peroxide, lauroyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, methyl ethyl ketone peroxide, cyclohexanone peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, and azobisisoheptonitrile. Preferably, the initiator is azobisisobutyronitrile and / or benzoyl peroxide.
[0111] According to the present invention, based on the total weight of the monomer represented by formula (1), the monomer represented by formula (2) and the monomer represented by formula (3), the amount of the initiator used is 0.1-5wt%, preferably 0.5-2wt%; in the present invention, if the proportion of the initiator is too low, the initiation reaction efficiency is low and the monomer residual rate is high; if the proportion of the initiator is too high, the reaction rate is too fast, which is easy to cause explosion, resulting in synthesis failure and low polymer molecular weight.
[0112] According to the present invention, the organic solvent is selected from one of ethyl acetate, acetone, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, anhydrous acetonitrile, anhydrous ethanol, chloroform, dichloromethane, carbon tetrachloride, dimethyl sulfoxide, cyclohexane, cyclohexanone, methyl ethyl ketone and methyl butyl ketone. Preferably, the organic solvent is one or more of ethyl acetate, N,N-dimethylformamide and N,N-dimethylacetamide.
[0113] According to the present invention, the mass ratio of the total amount of the monomer represented by formula (1), the monomer represented by formula (2) and the monomer represented by formula (3) to the amount of the organic solvent is (1-5): (5-10); in the present invention, if the mass ratio is too low, it will be unfavorable for the contact of the reaction monomers and the collision of free radicals, resulting in insufficient reaction and low reaction efficiency; if the mass ratio is too high, it may cause the reaction to be too fast, the viscosity of the late reaction product is too high, and it is not conducive to stirring.
[0114] According to the present invention, the mass ratio of the monomer represented by formula (1), the monomer represented by formula (2) and the monomer represented by formula (3) is (2-9): (1-7): (0.5-5), preferably (4-7): (2-5): (1-3); in the present invention, if the proportion of the monomer represented by formula (1) is too low, it is not conducive to the film formation of the polymer electrolyte, and if the proportion is too high, it is not conducive to the improvement of the room temperature ionic conductivity; if the content of the monomer represented by formula (2) is too low, the dissociation of lithium ions will be difficult, which is not conducive to the improvement of ionic conductivity; if the content is too high, the flexibility of the polymer electrolyte will be too poor, which is not conducive to film formation; if the content of the monomer represented by formula (3) is too low, it is not conducive to the voltage resistance performance of the polymer electrolyte, and if it is too high, it will cause poor flexibility of the polymer electrolyte.
[0115] According to the present invention, the conditions of the first reaction include: a reaction temperature of 25-100°C, preferably 50-80°C; a reaction time of 0.5-6h, preferably 2-4h; in the present invention, if the reaction temperature is too low, it is difficult to initiate a polymerization reaction, and the reaction efficiency is low; if the reaction temperature is too high, the initiation rate is too fast, which reduces the molecular weight of the polymer, and even causes implosion, resulting in reaction failure. If the reaction time is too short, it is easy to cause insufficient reaction and low monomer conversion efficiency; if the reaction time is too long, it will cause energy waste. More preferably, the first reaction is carried out under stirring conditions, and the stirring speed is 60-2000rpm, preferably 200-1000rpm; if the stirring speed is too low, it is not conducive to the full contact of the reaction monomers and reduces the reaction efficiency; if the stirring speed is too fast, it is easy to cause more active radicals of the initiator, more reactive sites, reduce the molecular weight of the polymer, and is not conducive to the film formation of the polymer electrolyte and the improvement of mechanical properties.
[0116] According to the present invention, in the preparation method described in the present invention, in the monomer represented by formula (II):
[0117]
[0118] Among them, preferably, 1≤m≤20, more preferably 5≤m≤10.
[0119] According to the present invention, in the preparation method described in the present invention, in the monomer represented by formula (III):
[0120]
[0121] Among them, preferably, 1≤p≤20, more preferably 5≤p≤10.
[0122] According to the present invention, in the preparation method described in the present invention, in the monomer represented by formula (IV):
[0123]
[0124] Wherein, preferably, 1≤n≤20, more preferably 5≤n≤10;
[0125] R 7 Preferred are one or more of methyl, ethyl, propyl, isopropyl, n-butyl and isobutyl, and more preferred is methyl.
[0126] According to the present invention, the ratio of the total mass of the monomers of formula (II), formula (III) and formula (IV) to the total mass of the monomers of formula (1) is (1-5):1, preferably (3-4):1; in the present invention, if the mass ratio is too low, the polymer electrolyte has fewer ion-conducting segments, which is not conducive to the transmission of lithium ions; if the mass ratio is too high, some monomers do not participate in the reaction, resulting in a waste of raw materials.
[0127] According to the present invention, the conditions of the second reaction include: a reaction temperature of 25-80°C, preferably 50-60°C; a reaction time of 2-12h, preferably 4-6h; in the present invention, if the reaction temperature is too low, the reaction efficiency is low; if the reaction temperature is too high, the initiation rate is too fast, and even leads to implosion, resulting in reaction failure. If the reaction time is too short, it is easy to cause insufficient reaction and low conversion efficiency of reactants; if the reaction time is too long, it will cause waste of energy consumption. More preferably, the second reaction is carried out under stirring conditions, and the stirring speed is 60-2000rpm, preferably 200-1000rpm; in the present invention, if the stirring speed is too low, it is not conducive to the full contact of the reactants and reduces the reaction efficiency; if the stirring speed is too fast, it is easy to cause splashing of the reactants, which is not conducive to the reaction.
[0128] The third aspect of the present invention provides a multi-polymer prepared by the above-mentioned preparation method.
[0129] A fourth aspect of the present invention provides a polymer electrolyte, wherein the polymer electrolyte comprises a polymer and a lithium salt, wherein the polymer is the multi-polymer described above.
[0130] According to the present invention, the lithium salt is selected from one or more of lithium fluoride, lithium chloride, lithium bromide, lithium iodide, lithium perchlorate, lithium aluminate, lithium nitrate, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethylsulfonate, lithium bis(trifluoromethylsulfonylimide), lithium bis(fluorosulfonylimide), lithium bis(polyfluoroalkoxysulfonylimide), lithium bis(polyfluoroalkylsulfonylimide), lithium thiocyanate, bis(trifluoromethylsulfonylalkyl)lithium, lithium trifluoromethyl carbonate, lithium methyl carbonate, lithium bis(trifluoromethyl)tetrafluoroborate, lithium dicyanoimide and lithium dioxalatoborate; preferably lithium difluorooxalatoborate and / or lithium bis(fluorosulfonylimide).
[0131] According to the present invention, based on the total mass of the polymer electrolyte, the content of the lithium salt is 5-50wt%, preferably 15-35wt%. In the present invention, too high a content of the lithium salt may easily lead to the polymer electrolyte being unable to form a film, thereby reducing the mechanical strength; too low a content of the lithium salt may be detrimental to the improvement of the room temperature ionic conductivity.
[0132] A fifth aspect of the present invention provides a solid-state lithium-ion battery, wherein the solid-state lithium-ion battery comprises a positive electrode sheet, a separator and a negative electrode sheet, wherein the separator is a polymer electrolyte membrane prepared from the aforementioned polymer electrolyte.
[0133] In the present invention, a certain mass of lithium salt is added to a polymer solution at room temperature and stirred until the lithium salt is completely dissolved to obtain a polymer electrolyte solution; the polymer electrolyte solution is poured into a mold or applied to a substrate and dried to remove the solvent to obtain a polymer electrolyte membrane.
[0134] In the present invention, the polymer electrolyte can be prepared into electrolyte membranes with different thicknesses according to usage requirements.
[0135] In the present invention, the preparation method of the electrolyte membrane is not particularly limited, and can be any one of casting, coating and spraying known in the industry.
[0136] According to the present invention, the thickness of the polymer electrolyte membrane is 5-150 μm, preferably 15-50 μm.
[0137] The present invention will be described in detail below through examples.
[0138] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are conventional products that can be obtained through commercial channels. The weight ratio of each structural unit contained in the obtained multi-polymer product is determined according to the raw material input amount.
[0139] Example 1
[0140] This example is to illustrate the multi-polymer and polymer electrolyte membrane prepared by the present invention.
[0141] 1) Weigh 14 g of ethyl isocyanate acrylate, 4 g of acrylonitrile, 2 g of allyl ethyl carbonate, and 0.4 g of initiator and mix them evenly. The initiator is azobisisobutyronitrile;
[0142] 2) slowly adding the mixed solution obtained in step 1) into a reaction vessel containing 180 g of ethyl acetate, stirring under a nitrogen atmosphere, and slowly raising the temperature inside the reaction vessel to the reaction temperature; the stirring speed is 500 rpm; the reaction temperature is 70° C.; and the reaction time is 4 h;
[0143] 3) Cooling to room temperature, slowly adding 5g of polyethylene glycol monomethyl ether (m=8) to the solution obtained in step 2), and slowly raising the temperature inside the reaction container to the reaction temperature. The stirring speed is 1000rpm; the reaction temperature is 50°C, and the reaction is continued for 6h; and the multi-polymer S-1 is obtained;
[0144] After testing, the multi-polymer S-1 contains structural unit A provided by ethyl isocyanate acrylate, structural unit B provided by acrylonitrile, and structural unit C provided by allyl ethyl carbonate, and the molar number a of structural unit A, the molar number b of structural unit B, and the molar number c of structural unit C satisfy:
[0145] a:b:c=5:3.8:0.8;
[0146] In addition, the multipolymer S-1 also contains a structural unit E provided by polyethylene glycol monomethyl ether (m=8), and the -OH in the polyethylene glycol monomethyl ether reacts with the -NCO in ethyl isocyanate to form an addition reaction; and in the multipolymer, the molar number a of the structural unit A and the molar number e of the structural unit E satisfy 10:1.
[0147] 4) cooling to room temperature, adding 6.25 g of lithium salt lithium bis(fluorosulfonyl)imide to the mixed solution obtained in step 3), stirring until the lithium salt is completely dissolved, to obtain a polymer electrolyte solution;
[0148] 5) Pour the polymer electrolyte solution obtained in step 4) into a mold to remove the solvent to obtain a polymer electrolyte membrane.
[0149] The thickness of the polymer electrolyte membrane was 50 μm.
[0150] in addition, Figure 1 The LSV curve of the polymer electrolyte membrane prepared in Example 1 is shown in FIG. Figure 1 It can be seen that the polymer electrolyte membrane has a relatively high electrochemical window of about 4.5V.
[0151] Example 2
[0152] This example is to illustrate the multi-polymer and polymer electrolyte membrane prepared by the present invention.
[0153] 1) Weigh 8g of ethyl isocyanate acrylate, 10g of acrylonitrile, 6g of allyl ethyl carbonate, and 0.2g of initiator and mix them evenly, wherein the initiator is azobisisobutyronitrile;
[0154] 2) slowly adding the mixed solution obtained in step 1) into a reaction vessel containing 36 g of N,N-dimethylformamide, stirring under a nitrogen atmosphere, and slowly raising the temperature inside the reaction vessel to the reaction temperature; the stirring speed is 800 rpm; the reaction temperature is 80° C.; and the reaction time is 3 h;
[0155] 3) Cooling to room temperature, slowly adding 8g of methoxy polyethylene glycol amine (p=8) to the solution obtained in step 2), and slowly raising the temperature inside the reaction container to the reaction temperature. The stirring speed is 1000rpm; the reaction temperature is 60°C, and the reaction is continued for 4h; and the multi-polymer S-2 is obtained;
[0156] After testing, the multi-polymer S-2 contains structural unit A provided by ethyl isocyanate acrylate, structural unit B provided by acrylonitrile, and structural unit C provided by allyl ethyl carbonate, and the molar number a of structural unit A, the molar number b of structural unit B, and the molar number c of structural unit C satisfy:
[0157] a:b:c=5:16:4;
[0158] In addition, the multipolymer S-2 further comprises a structural unit F provided by methoxy polyethylene glycol amine (p=8), wherein -NH 2 An addition reaction is carried out with -NCO in ethyl isocyanate; and in the multi-polymer, the molar number a of the structural unit A and the molar number f of the structural unit F satisfy 0.8:1.
[0159] 4) cooling to room temperature, adding 15 g of lithium salt lithium difluorooxalate borate to the mixed solution obtained in step 3), stirring until the lithium salt is completely dissolved, to obtain a polymer electrolyte solution;
[0160] 5) Pour the polymer electrolyte solution obtained in step 4) into a mold to remove the solvent to obtain a polymer electrolyte membrane.
[0161] The thickness of the polymer electrolyte membrane was 25 μm.
[0162] in addition, Figure 2 This is a schematic diagram of the LSV curve of the polymer electrolyte membrane prepared in Example 2. Figure 1 It can be seen that the polymer electrolyte membrane has a relatively high electrochemical window of about 4.4V.
[0163] Example 3
[0164] This example is to illustrate the multi-polymer and polymer electrolyte membrane prepared by the present invention.
[0165] 1) Weigh 12g of ethyl isocyanate acrylate, 6g of methacrylonitrile, 4g of allyl ethyl carbonate, and 0.1g of initiator and mix them evenly, wherein the initiator is benzoyl peroxide;
[0166] 2) slowly adding the mixed solution obtained in step 1) into a reaction vessel containing 50 g of N,N-dimethylacetamide, stirring under a nitrogen atmosphere, and slowly raising the temperature inside the reaction vessel to the reaction temperature; the stirring speed is 200 rpm; the reaction temperature is 80° C.; and the reaction time is 3 h;
[0167] 3) Cooling to room temperature, slowly adding 6.5 g of polyethylene glycol monoacetate (n=8) to the solution obtained in step 2), and slowly raising the temperature inside the reaction container to the reaction temperature. The stirring speed is 800 rpm; the reaction temperature is 55°C, and the reaction is continued for 5 hours; and the multi-polymer S-3 is obtained;
[0168] After testing, the multi-polymer S-3 contains structural unit A provided by ethyl isocyanate acrylate, structural unit B provided by methacrylonitrile, and structural unit C provided by allyl ethyl carbonate, and the molar number a of structural unit A, the molar number b of structural unit B, and the molar number c of structural unit C satisfy:
[0169] a:b:c=7.7:7.9:2.8;
[0170] In addition, the multipolymer S-3 also contains a structural unit G provided by polyethylene glycol monoacetate (n=8), and the -OH in the polyethylene glycol monoacetate (n=8) undergoes an addition reaction with the -NCO in ethyl isocyanate; and in the multipolymer, the molar number a of the structural unit A and the molar number g of the structural unit G satisfy 5.5:1.
[0171] 4) cooling to room temperature, adding 6 g of lithium salt lithium difluorooxalate borate to the mixed solution obtained in step 3), stirring until the lithium salt is completely dissolved, to obtain a polymer electrolyte solution;
[0172] 5) Pour the polymer electrolyte solution obtained in step 4) into a mold to remove the solvent to obtain a polymer electrolyte membrane.
[0173] The thickness of the polymer electrolyte membrane was 35 μm.
[0174] Example 4
[0175] This example is to illustrate the multi-polymer and polymer electrolyte membrane prepared by the present invention.
[0176] 1) Weigh 10g of ethyl isocyanate methacrylate, 6g of methacrylonitrile, 2g of allylphenyl carbonate, and 0.2g of initiator and mix them evenly. The initiator is azobisisobutyronitrile;
[0177] 2) slowly adding the mixed solution obtained in step 1) into a reaction vessel containing 72 g of N,N-dimethylformamide, stirring under a nitrogen atmosphere, and slowly raising the temperature inside the reaction vessel to the reaction temperature; the stirring speed is 500 rpm; the reaction temperature is 75° C.; and the reaction time is 4 h;
[0178] 3) Cooling to room temperature, slowly adding 6 g of polyethylene glycol monomethyl ether (m=9) to the solution obtained in step 2), and slowly raising the temperature inside the reaction container to the reaction temperature. The stirring speed is 600 rpm; the reaction temperature is 50°C, and the reaction is continued for 6 hours to obtain multi-polymer S-4;
[0179] After testing, the multi-polymer S-4 contains structural unit A provided by ethyl isocyanate methacrylate, structural unit B provided by methacrylonitrile, and structural unit C provided by allylphenyl carbonate, and the molar number a of structural unit A, the molar number b of structural unit B, and the molar number c of structural unit C satisfy:
[0180] a:b:c=5.8:8:1.1;
[0181] In addition, the multipolymer S-4 also contains a structural unit E provided by polyethylene glycol monomethyl ether (m=9), and the -OH in the polyethylene glycol monomethyl ether (m=9) undergoes an addition reaction with the -NCO in ethyl isocyanate methacrylate; and in the multipolymer, the molar number a of the structural unit A and the molar number e of the structural unit E satisfy 6:1.
[0182] 4) cooling to room temperature, adding 10 g of lithium salt lithium difluorooxalate borate to the mixed solution obtained in step 3), stirring until the lithium salt is completely dissolved, to obtain a polymer electrolyte solution;
[0183] 5) Pour the polymer electrolyte solution obtained in step 4) into a mold to remove the solvent to obtain a polymer electrolyte membrane.
[0184] The thickness of the polymer electrolyte membrane was 50 μm.
[0185] Example 5
[0186] This example is to illustrate the multi-polymer and polymer electrolyte membrane prepared by the present invention.
[0187] 1) Weigh 14 g of ethyl isocyanate methacrylate, 4 g of 2-fluoroacrylonitrile, 4 g of allyl methyl carbonate, and 0.3 g of initiator and mix them evenly. The initiator is azobisisobutyronitrile;
[0188] 2) slowly adding the mixed solution obtained in step 1) into a reaction vessel containing 40 g of N,N-dimethylformamide, stirring under a nitrogen atmosphere, and slowly raising the temperature inside the reaction vessel to the reaction temperature; the stirring speed is 500 rpm; the reaction temperature is 75° C.; and the reaction time is 4 h;
[0189] 3) Cooling to room temperature, slowly adding 6.5 g of polyethylene glycol monomethyl ether (m=9) to the solution obtained in step 2), and slowly raising the temperature inside the reaction container to the reaction temperature. The stirring speed is 600 rpm; the reaction temperature is 50°C, and the reaction is continued for 6 hours to obtain the multi-polymer S-5;
[0190] After testing, the multi-polymer S-5 contains structural unit A provided by ethyl isocyanate methacrylate, structural unit B provided by 2-fluoroacrylonitrile, and structural unit C provided by allyl methyl carbonate, and the molar number a of structural unit A, the molar number b of structural unit B, and the molar number c of structural unit C satisfy:
[0191] a:b:c=8:5:3;
[0192] In addition, the multipolymer S-5 also contains a structural unit E provided by polyethylene glycol monomethyl ether (m=9), and the -OH in the polyethylene glycol monomethyl ether (m=9) undergoes an addition reaction with the -NCO in ethyl isocyanate methacrylate; and in the multipolymer, the molar number a of the structural unit A and the molar number e of the structural unit E satisfy 6:1.
[0193] 4) cooling to room temperature, adding 10 g of lithium salt lithium bis(fluorosulfonyl)imide to the mixed solution obtained in step 3), stirring until the lithium salt is completely dissolved, to obtain a polymer electrolyte solution;
[0194] 5) Pour the polymer electrolyte solution obtained in step 4) into a mold to remove the solvent to obtain a polymer electrolyte membrane.
[0195] The thickness of the polymer electrolyte membrane was 50 μm.
[0196] Example 6
[0197] This example is to illustrate the multi-polymer and polymer electrolyte membrane prepared by the present invention.
[0198] A multi-polymer was prepared in the same manner as in Example 1, except that: in step 1), "14 g of ethyl isocyanate acrylate, 4 g of acrylonitrile, and 2 g of allyl ethyl carbonate" was replaced with "14 g of ethyl isocyanate methacrylate, 4 g of methacrylonitrile, and 2 g of allyl methyl carbonate";
[0199] And replace "5 g polyethylene glycol monomethyl ether (m=8)" in step 3) with "5 g polyethylene glycol monoacetate (n=8)";
[0200] As a result, multi-polymer S-6 was obtained;
[0201] After testing, the multi-polymer S-6 contains structural unit A provided by ethyl isocyanate methacrylate, structural unit B provided by methacrylonitrile, and structural unit C provided by allyl methyl carbonate, and the molar number a of structural unit A, the molar number b of structural unit B, and the molar number c of structural unit C satisfy:
[0202] a:b:c=7:5:1;
[0203] In addition, the multipolymer S-6 also contains a structural unit G provided by polyethylene glycol monoacetate (n=8), and the -OH in the polyethylene glycol monoacetate (n=8) undergoes an addition reaction with the -NCO in ethyl isocyanate methacrylate; and in the multipolymer, the molar number a of the structural unit A and the molar number e of the structural unit E satisfy 7:1.
[0204] In addition, a polymer electrolyte membrane was prepared in the same manner as in Example 1. The thickness of the polymer electrolyte membrane was 80 μm.
[0205] Example 7
[0206] This example is to illustrate the multi-polymer and polymer electrolyte membrane prepared by the present invention.
[0207] A multi-component copolymer was prepared in the same manner as in Example 2, except that: in step 1), "8 g of ethyl isocyanate acrylate, 10 g of acrylonitrile, and 6 g of allyl ethyl carbonate" was replaced with "8 g of ethyl isocyanate methacrylate, 10 g of methacrylonitrile, and 6 g of allyl phenyl carbonate";
[0208] And replace "8 g methoxypolyethylene glycol amine (p=8)" in step 3) with "8 g polyethylene glycol monoacetate (n=8)";
[0209] As a result, multi-polymer S-7 was obtained;
[0210] After testing, the multi-polymer S-7 contains structural unit A provided by ethyl isocyanate methacrylate, structural unit B provided by methacrylonitrile, and structural unit C provided by allylphenyl carbonate, and the molar number a of structural unit A, the molar number b of structural unit B, and the molar number c of structural unit C satisfy:
[0211] a:b:c=5.7:14.7:3.7;
[0212] In addition, the multipolymer S-7 also contains a structural unit G provided by polyethylene glycol monoacetate (n=8), wherein -OH in the polyethylene glycol monoacetate (n=8) undergoes an addition reaction with -NCO in ethyl isocyanate methacrylate; and in the multipolymer, the molar number a of the structural unit A and the molar number f of the structural unit F satisfy 2.8:1.
[0213] In addition, a polymer electrolyte membrane was prepared in the same manner as in Example 1. The thickness of the polymer electrolyte membrane was 50 μm.
[0214] Example 8
[0215] This example is to illustrate the multi-polymer and polymer electrolyte membrane prepared by the present invention.
[0216] A multi-polymer was prepared in the same manner as in Example 3, except that: in step 1), "12 g of ethyl isocyanate acrylate, 6 g of methacrylonitrile, and 4 g of allyl ethyl carbonate" was replaced with "12 g of ethyl isocyanate methacrylate, 6 g of acrylonitrile, and 4 g of allyl phenyl carbonate";
[0217] And replace "6.5 g polyethylene glycol monoacetate (n=8)" in step 3) with "6.5 g polyethylene glycol monomethyl ether (m=9)";
[0218] As a result, multi-polymer S-8 was obtained;
[0219] After testing, the multi-polymer S-8 contains structural unit A provided by ethyl isocyanate methacrylate, structural unit B provided by acrylonitrile, and structural unit C provided by allylphenyl carbonate, and the molar number a of structural unit A, the molar number b of structural unit B, and the molar number c of structural unit C satisfy:
[0220] a:b:c=7.7:11.3:2.4;
[0221] In addition, the multipolymer S-8 also contains a structural unit E provided by polyethylene glycol monomethyl ether (m=9), and the -OH in the polyethylene glycol monomethyl ether (m=9) undergoes an addition reaction with the -NCO in ethyl isocyanate methacrylate; and in the multipolymer, the molar number a of the structural unit A and the molar number e of the structural unit E satisfy 5:1.
[0222] In addition, a polymer electrolyte membrane was prepared in the same manner as in Example 1. The thickness of the polymer electrolyte membrane was 50 μm.
[0223] Comparative Example 1
[0224] The comparative polymer electrolyte was prepared according to the following steps and methods:
[0225] 1) Weigh 20 g of polyethylene oxide (PEO) and dissolve it in 80 g of anhydrous acetonitrile to prepare a polymer solution;
[0226] 2) adding 5 g of lithium salt lithium bis(fluorosulfonyl)imide to the polymer solution of step 1), stirring until the lithium salt is completely dissolved, to obtain a polymer electrolyte solution;
[0227] 3) Pour the polymer electrolyte solution obtained in step 2) into a mold to remove the solvent, thereby obtaining a polymer electrolyte membrane.
[0228] The thickness of the polymer electrolyte membrane was 50 μm.
[0229] in addition, Figure 3 is a schematic diagram of the LSV curve of the polymer electrolyte membrane prepared in Comparative Example 1. Figure 3 It can be seen that the electrolyte membrane described in Comparative Example 1 has a lower electrochemical window of about 4.0V.
[0230] Comparative Example 2
[0231] The comparative polymer electrolyte was prepared according to the following steps and methods:
[0232] 1) Weigh 20 g of polyethylene oxide (PEO) and dissolve it in 80 g of anhydrous acetonitrile to prepare a polymer solution;
[0233] 2) adding 10 g of lithium salt lithium bis(fluorosulfonyl)imide to the polymer solution of step 1), stirring until the lithium salt is completely dissolved, to obtain a polymer electrolyte solution;
[0234] 3) Pour the polymer electrolyte solution obtained in step 2) into a mold to remove the solvent, thereby obtaining a polymer electrolyte membrane.
[0235] The thickness of the polymer electrolyte membrane was 100 μm.
[0236] Comparative Example 3
[0237] The same method as in Example 1 was used to prepare the product except that: in step 1), "14 g ethyl isocyanate acrylate, 4 g acrylonitrile, 2 g allyl ethyl carbonate" was replaced with "4 g acrylonitrile, 2 g allyl ethyl carbonate";
[0238] As a result, multi-polymer D-3 was obtained;
[0239] After testing, the multi-polymer D-3 contains a structural unit B provided by acrylonitrile and a structural unit C provided by allyl ethyl carbonate, and the molar number b of the structural unit B and the molar number c of the structural unit C satisfy:
[0240] b:c=5:1.
[0241] In addition, since the multi-polymer D-3 does not contain ethyl isocyanate methacrylate, it cannot chemically react with polyethylene glycol monomethyl ether and can only be physically blended with polyethylene glycol monomethyl ether.
[0242] In addition, the polymer electrolyte membrane was prepared in the same manner as in Example 1, but the film-forming effect was poor and a continuous and stable self-supporting membrane could not be formed.
[0243] Comparative Example 4
[0244] Prepared in the same manner as in Example 1 except that: in step 1), "14 g ethyl isocyanate acrylate, 4 g acrylonitrile, 2 g allyl ethyl carbonate" was replaced with "14 g ethyl isocyanate acrylate, 2 g allyl ethyl carbonate";
[0245] As a result, multi-polymer D-4 was obtained;
[0246] After testing, the multi-polymer D-4 contains the structural unit A provided by ethyl isocyanate acrylate and the structural unit C provided by allyl ethyl carbonate, and the molar number a of the structural unit A and the molar number c of the structural unit C satisfy:
[0247] a:c=6.5:1.
[0248] In addition, since the multipolymer D-4 does not contain acrylonitrile, it does not contain a strongly polar functional group and cannot effectively promote the dissociation of the lithium salt, and the room temperature ionic conductivity is relatively low.
[0249] In addition, a polymer electrolyte membrane was prepared in the same manner as in Example 1. The thickness of the polymer electrolyte membrane was 50 μm.
[0250] Comparative Example 5
[0251] Prepared in the same manner as in Example 1 except that: in step 1), "14 g ethyl isocyanate acrylate, 4 g acrylonitrile, 2 g allyl ethyl carbonate" was replaced with "14 g ethyl isocyanate acrylate, 4 g acrylonitrile";
[0252] As a result, multi-polymer D-5 was obtained;
[0253] After testing, the multi-polymer D-5 contains the structural unit A provided by ethyl isocyanate acrylate and the structural unit B provided by acrylonitrile, and the molar number a of the structural unit A and the molar number b of the structural unit B satisfy:
[0254] a:b=6.6:15.
[0255] In addition, since the multi-polymer D-5 does not contain allyl ethyl carbonate, it lacks a group with high withstand voltage, and the electrolyte has a low electrochemical window.
[0256] In addition, a polymer electrolyte membrane was prepared in the same manner as in Example 1. The thickness of the polymer electrolyte membrane was 50 μm.
[0257] Comparative Example 6
[0258] This example is to illustrate the multi-polymer and polymer electrolyte membrane prepared by the present invention.
[0259] A multi-polymer was prepared in the same manner as in Example 1, except that step 3) was not performed;
[0260] Obtain multi-polymer D-6;
[0261] After testing, the multi-polymer D-6 contains structural unit A provided by ethyl isocyanate acrylate, structural unit B provided by acrylonitrile, and structural unit C provided by allyl ethyl carbonate, and the molar number a of structural unit A, the molar number b of structural unit B, and the molar number c of structural unit C satisfy:
[0262] a:b:c=5:3.8:0.8.
[0263] In addition, a polymer electrolyte membrane was prepared in the same manner as in Example 1. The polymer electrolyte membrane was hard and brittle, and had poor film-forming properties and flexibility. It was unable to form a continuous and stable electrolyte membrane and was therefore unusable.
[0264] Comparative Example 7
[0265] This example is to illustrate the multi-polymer and polymer electrolyte membrane prepared by the present invention.
[0266] The multi-polymer was prepared in the same manner as in Example 2, except that step 3) was not performed;
[0267] Obtain multi-polymer D-7;
[0268] After testing, the multi-polymer D-7 contains structural unit A provided by ethyl isocyanate acrylate, structural unit B provided by acrylonitrile, and structural unit C provided by allyl ethyl carbonate, and the molar number a of structural unit A, the molar number b of structural unit B, and the molar number c of structural unit C satisfy:
[0269] a: b: c = (5): (16): (4).
[0270] In addition, a polymer electrolyte membrane was prepared in the same manner as in Example 2. The polymer electrolyte membrane was hard and brittle, and had poor film-forming properties and flexibility. It was unable to form a continuous and stable electrolyte membrane and was therefore unusable.
[0271] Test Case
[0272] (1) The room temperature ionic conductivity of the polymer electrolyte was tested by EIS method:
[0273] The polymer electrolyte membranes prepared in the examples and comparative examples were cut into discs with a diameter of 18 mm, respectively, and then sandwiched between two stainless steel electrodes (SS) to form SS / SPE / SS blocking electrodes. The ionic conductivity of the electrolyte was indirectly obtained by testing the AC impedance spectrum of the blocking electrode using an electrochemical workstation. The AC impedance spectrum test frequency range was 10 6 HZ—0.1HZ. Ionic conductivity (σ) is calculated by the following formula:
[0274] σ=L / (R×S)
[0275] Where R (Ω) is the resistance of the sample, L (cm) is the thickness of the sample, S (cm 2 ) is the area of the sample. The thickness of the sample is measured by a thickness gauge.
[0276] (2) The electrochemical window of the polymer electrolyte membrane is evaluated using the linear sweep (LSV) method. The linear sweep (LSV) curve of the polymer-based electrolyte membrane is tested using an electrochemical workstation:
[0277] Stainless steel was used as the working electrode, and metallic lithium was used as the counter electrode and reference electrode. The linear scan range was from open circuit voltage to 5.5 V (vs. Li / Li+) at a scan rate of 0.5 mV / s.
[0278] The room temperature ionic conductivity and electrochemical window of the polymer electrolyte membranes prepared in Examples 1-8 and Comparative Examples 1-5 are shown in Table 1.
[0279] Table 1 Room temperature ionic conductivity and electrochemical window of polymer electrolytes
[0280] project Room temperature ionic conductivity (S / cm) Electrochemical Window (V) Example 1 <![CDATA[7.65×10 -5 ]]> 4.5 Example 2 <![CDATA[4.28×10 -5 ]]> 4.4 Example 3 <![CDATA[5.21×10 -5 ]]> 4.6 Example 4 <![CDATA[6.58×10 -5 ]]> 4.5 Example 5 <![CDATA[1.21×10 -4 ]]> 4.2 Example 6 <![CDATA[6.35×10 -5 ]]> 4.4 Example 7 <![CDATA[3.58×10 -5 ]]> 4.4 Example 8 <![CDATA[4.30×10 -5 ]]> 4.5 Comparative Example 1 <![CDATA[5.22×10 -7 ]]> 4.0 Comparative Example 2 <![CDATA[2.65×10 -6 ]]> 3.9 Comparative Example 4 <![CDATA[5.65×10 -6 ]]> 4.2 Comparative Example 5 <![CDATA[1.68×10 -5 ]]> 3.8
[0281] It can be seen from Table 1 that the room temperature ionic conductivity of the polymer electrolyte membrane prepared in the embodiments of the present invention is higher than that of the comparative example, which shows that the polymer electrolyte prepared in the present invention has a higher room temperature ionic conductivity; in addition, the electrochemical window of the polymer electrolyte prepared in the embodiments is higher than that of the comparative example, which shows that the polymer electrolyte prepared in the present invention has excellent voltage resistance characteristics, has a higher electrochemical window, and can match a higher voltage battery system.
[0282] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A multi-component copolymer, characterized in that: The multi-component copolymer includes structural unit A, structural unit B and structural unit C, and the multi-component copolymer further includes at least one of structural unit E, structural unit F and structural unit G; Wherein, the structural unit A has a structure shown in formula (a), the structural unit B has a structure shown in formula (b), and the structural unit C has a structure shown in formula (c); Wherein, in formula (a), R1 is a C2-C4 alkyl group; R2 is H and / or a C1-C4 alkyl group; In formula (b), R3 is selected from one or more of H, F, Cl, Br, I, methyl, ethyl and phenyl; R4 is selected from one or more of H, methoxy, ethoxy, cyclopentyl, phenyl and p-fluoro-substituted phenyl; In formula (c), R5 is H and / or a C1-C4 alkyl group; R6 is one or more of a phenyl group, a C1-C4 alkyl group and a fluoroalkyl group; The structural unit E is provided by a polymer represented by formula (II); Wherein, m is a natural number greater than or equal to 1; The structural unit F is provided by a polymer represented by formula (III); Wherein, p is a natural number greater than or equal to 1; The structural unit G is provided by a polymer represented by formula (IV); Wherein, n is a natural number greater than or equal to 1, and R7 is a C1-C4 alkyl group.
2. The multi-component copolymer according to claim 1, wherein R1 is one or more of ethyl, propyl and butyl; R2 is selected from one or more of H, methyl, ethyl, propyl, isopropyl, n-butyl and isobutyl, preferably H and / or methyl; R3 is selected from one or more of methyl, H and F; R4 is selected from one or more of H, methoxy, ethoxy and cyclopentyl; R5 is selected from one or more of H, methyl, ethyl, propyl and butyl, preferably H and / or methyl; R6 is selected from one or more of phenyl, methyl, ethyl, propyl, butyl and -CF3, preferably methyl and / or -CF3.
3. The multi-component copolymer according to claim 1 or 2, wherein: The structural unit A is derived from monomer a, and the monomer a is preferably alkyl isocyanate acrylate, more preferably at least one of ethyl isocyanate acrylate, propyl isocyanate acrylate, ethyl isocyanate methacrylate and propyl isocyanate methacrylate, and most preferably ethyl isocyanate acrylate and / or ethyl isocyanate methacrylate; And / or, the structural unit B is derived from monomer b, and the monomer b is preferably an acrylonitrile monomer, more preferably at least one of acrylonitrile, methacrylonitrile, 2-fluoroacrylonitrile, 2-chloroacrylonitrile, 2-phenylacrylonitrile, 3-cyclopentylacrylonitrile, 3-methoxyacrylonitrile, 3-ethoxyacrylonitrile and 3-(4-fluorophenyl)-2-acrylonitrile, and most preferably at least one of acrylonitrile, methacrylonitrile and 2-fluoroacrylonitrile; And / or, the structural unit C is derived from a monomer c, and the monomer c is preferably a linear unsaturated carbonate monomer, more preferably at least one of allyl methyl carbonate, allyl ethyl carbonate, allyl propyl carbonate, allyl butyl carbonate, and allyl phenyl carbonate, and most preferably at least one of allyl ethyl carbonate, allyl phenyl carbonate, and allyl methyl carbonate.
4. The multi-component copolymer according to claim 1 or 2, wherein In the multi-polymer, the molar ratio of the structural unit A, the structural unit B and the structural unit C is (2-9): (2-21): (0.5-8), preferably (3-8): (3-18): (0.75-5).
5. The multi-polymer according to any one of claims 1 to 4, wherein: 1≤m≤20, preferably 5≤m≤10; Preferably, in the multi-polymer, the molar ratio of the structural unit A to the structural unit E is (0.5-10):
1.
6. The multi-polymer according to any one of claims 1 to 5, wherein: 1≤p≤20, preferably 5≤p≤10; Preferably, in the multi-polymer, the molar ratio of the structural unit A to the structural unit F is (0.5-10):
1.
7. The multi-polymer according to any one of claims 1 to 6, wherein: 1≤n≤20, preferably 5≤n≤10; Preferably, R7 is one or more of methyl, ethyl, propyl, isopropyl, n-butyl and isobutyl, more preferably methyl; Preferably, in the multi-polymer, the molar ratio of the structural unit A to the structural unit G is (0.5-10):
1.
8. A method for preparing a multi-component copolymer, characterized in that: The preparation method comprises: 1) in the presence of an initiator and an organic solvent, contacting a monomer represented by formula (1), a monomer represented by formula (2) and a monomer represented by formula (3) to carry out a first reaction to obtain a first reaction product; Wherein, in formula (1), R1 is a C2-C4 alkyl group; R2 is H and / or a C1-C4 alkyl group; In formula (2), R3 is selected from one or more of H, F, Cl, Br, I, methyl, ethyl and phenyl; R4 is selected from one or more of H, methoxy, ethoxy, cyclopentyl, phenyl and p-fluoro-substituted phenyl; In formula (3), R5 is H and / or a C1-C4 alkyl group; R6 is one or more of a phenyl group, a C1-C4 alkyl group and a fluoroalkyl group; 2) contacting the first reaction product with at least one of the monomers represented by formula (II), formula (III) and formula (IV) to carry out a second reaction to obtain a multi-component copolymer; Wherein, m is a natural number greater than or equal to 1; Wherein, p is a natural number greater than or equal to 1; Wherein, n is a natural number greater than or equal to 1; and R7 is a C1-C4 alkyl group.
9. The preparation method according to claim 8, wherein: R1 is one or more of ethyl, propyl and butyl; R2 is selected from one or more of H, methyl, ethyl, propyl, isopropyl, n-butyl and isobutyl, preferably H and / or methyl; R3 is selected from one or more of methyl, H and F; R4 is selected from one or more of H, methoxy, ethoxy and cyclopentyl; R5 is selected from one or more of H, methyl, ethyl, propyl and butyl, preferably H and / or methyl; R6 is selected from one or more of phenyl, methyl, ethyl, propyl, butyl and -CF3, preferably methyl and / or -CF3.
10. The preparation method according to claim 8 or 9, wherein: The initiator is an oil-soluble initiator; And / or, based on the total weight of the monomer represented by formula (1), the monomer represented by formula (2) and the monomer represented by formula (3), the amount of the initiator is 0.1-5wt%, preferably 0.5-2wt%; and / or, the mass ratio of the total amount of the monomer represented by formula (1), the monomer represented by formula (2) and the monomer represented by formula (3) to the amount of the organic solvent is (1-5):(5-10); and / or, the mass ratio of the monomer represented by formula (1), the monomer represented by formula (2) and the monomer represented by formula (3) is (2-9): (1-7): (0.5-5), preferably (4-7): (2-5): (1-3); And / or, the conditions of the first reaction include: reaction temperature of 25-100° C., reaction time of 0.5-6 h.
11. The preparation method according to any one of claims 8 to 10, wherein: 1≤m≤20, preferably 5≤m≤10; Preferably, 1≤p≤20, more preferably 5≤p≤10; Preferably, 1≤n≤20, more preferably 5≤n≤10; Preferably, R7 is one or more of methyl, ethyl, propyl, isopropyl, n-butyl and isobutyl, more preferably methyl.
12. The preparation method according to claim 11, wherein The ratio of the total mass of the monomers of formula (II), formula (III), and formula (IV) to the total mass of the monomers of formula (1) is (1-5):1, preferably (3-4):1; And / or, the conditions of the second reaction include: the reaction temperature is 25-80° C., and the reaction time is 2-12 h.
13. A multi-polymer prepared by the preparation method according to any one of claims 8 to 12.
14. A polymer electrolyte, characterized in that The polymer electrolyte comprises a polymer and a lithium salt, wherein the polymer is the multi-polymer according to any one of claims 1-7 and 13.
15. The polymer electrolyte according to claim 14, wherein Based on the total mass of the polymer electrolyte, the content of the lithium salt is 5-50wt%, preferably 15-35wt%.
16. A solid-state lithium-ion battery, characterized in that: The solid-state lithium-ion battery comprises a positive electrode sheet, a separator and a negative electrode sheet, wherein the separator is a polymer electrolyte membrane prepared from the polymer electrolyte according to claim 14 or 15.
17. The solid-state lithium-ion battery according to claim 16, wherein: The thickness of the polymer electrolyte membrane is 5-150 μm, preferably 15-50 μm.
Citation Information
Patent Citations
Binder composition for rechargeable lithium battery, and electrode and rechargeable lithium battery including the same
CN102412401A
All-solid polymer electrolyte membrane and preparation method thereof
CN106992311A
